Assessment Of The Process Of Acetylation And Lipid Composition Of Blood In Patients With Chronic Periodontitis Against The Background Of Viral Hepatitis C - Abduyusupova K.M; Khaidarov A.M; Khadzhimetov A.A; Khaidarova S.E (Zien Journals, 2024)
The purpose of this study was to study the relationship between alel variants of acetylation and the lipid composition of blood in patients with chronic periodontitis against the background of viral hepatitis C. Biochemical studies were carried out in 42 people aged 18-45 years (24 men and 18 women) diagnosed with chronic periodontitis against the background of chronic hepatitis C. The phenotype of acetylation in saliva and the lipid spectrum of blood were studied. The prevalence of the disease among patients with slow type of acetylation in saliva was noted at an average of 17% in the examined patients of the study group. In patients with slow type of acetylation, a high level of triglycerides was noted, which was accompanied by a low concentration of cholesterol, high and low density lipoproteins in the blood
Keywords: chronic generalized periodontitis; viral hepatitis C; acetylation phenotype